Sustainability of CO2 replacement processes in marine hydrate reservoirs: Factors causing changes on mechanical properties of Gas-Hydrate after CO2/CH4 exchange - Fabio Trippetta; Alberto Maria Gambelli; Beatrice Castellani; Giorgio Minelli; Federico Rossi (Process Safety and Environmental Protection, 2023)
The energy content of Gas Hydrated in form of natural gas is approximately twice with respect to the total energy still producible from all the known conventional energy sources. To reduce the risk induced by exploitation of hydrate reservoirs a good knowledge of the mechanical properties is crucial. Here we simulate CH4 replacement with CO2 and then we analyze the mechanical properties of replaced hydrates through porosity, Vp and Vs measurements. Replacement tests with CO2 have been performed by depressurization and thermal stimulation. Both procedures result in a final CH4/CO2 concentration of ∼30/70%. We then measured the petrophysical properties of pure CO2 and CH4/CO2 hydrates hosted in synthetic (Glass beads -GB) and natural sand (Iceland Sand-IS). Porosity and velocity within the same hosting sediments, show a clear inverse relation for the sub-angular and poorly sorted IS being this less evident for the spherical and highly sorted GB sands. CO2 replacement increases Vp and dynamic Young's modulus for GB samples whilst IS are less influenced by the presence of CO2. These results demonstrate that reservoir sediments severely affect the mechanical properties of hydrates and thus their characteristics must be taken in account for safety well and reservoir management.